EFFECTIVENESS OF RESPIRATORY REHABILITATION FOR POMPE PATIENTS (Vietnam Journal of Community Medicine, 2021)
Objectives: To assess the effectiveness of respiratory rehabilitation for Pompe patients at National Hospital of Pediatrics. Subjects and methods: The non-controlled clinical intervention study of 21 Pompe patients who were treated for rehabilitation at National Hospital of Pediatrics. All patients were objectively evaluated before and after 4 weeks of intervention. Result: In this study, there were statistically significant improvements of respiratory and motor development over 4 weeks of treatment (p < 0,05), with heartbeats from 98,57 ± 10,92 down to 94,29 ± 10,16 points; breathiness from 33,21 ± 8,68 down to 30,43 ± 7,46 points; SpO2 from 96,14 ± 1,10 up to 96,79 ± 0,98 points; % GMFM from 55,43 ± 33,23 up to 58,05 ± 32,87 percent. Conclusions: There were improvements of respiratory and motor development for Pompe patients after intervention.
Keywords: Rehabilitation, respiratory, Pompe.